VGLL1 contributes to both the transcriptome and epigenome of the developing trophoblast compartment - Ruben I. Calderon; Nirvay Sah; Molly Huang; Sampada Kallol; Ryan H. Kittle; Walee B. Shaik; Ahmed Abdelbaki; Jennifer N. Chousal; Robert Morey; Tony Bui; Alejandra Mitre; Norah M. E. Fogarty; et al. (Proceedings of the National Academy of Sciences, 2025)
The trophectoderm (TE), the first lineage specified during mammalian development, initiates implantation and gives rise to placental trophoblasts. While animal models have elucidated key conserved signaling pathways involved in early TE specification, including bone morphogenetic protein (BMP), WNT, and HIPPO, species-specific differences during early development emphasize the need for human-specific models. We previously identified VGLL1, a coactivator of TEAD transcription factors, as a human-specific placental marker. In this study, we employed a pluripotent stem cell (PSC)-based model of TE induction by BMP4 to investigate chromatin remodeling and transcriptional dynamics during TE formation. BMP4-induced chromatin accessibility changes promoted a trophoblast gene expression program, while mesoderm lineage markers were only transiently expressed upon canonical WNT activation. We found that VGLL1 was expressed downstream of key TE transcription factors (GATA2/3, TFAP2A/C) but was essential for establishment of full trophoblast identity by up-regulating the epidermal growth factor receptor (EGFR) and reinforcing GATA3 expression through positive feedback. Notably, VGLL1 enhanced canonical WNT signaling via direct regulation of WNT receptors and effectors. We also identified KDM6B, a histone demethylase that removes H3K27me3 repressive marks, as a direct VGLL1 target. KDM6B facilitated activation of bivalent promoters associated with TE markers, linking epigenetic regulation to lineage identity. Our findings establish a mechanistic framework positioning VGLL1 as a central regulator that integrates HIPPO, BMP, and WNT signaling pathways to drive establishment of human TE.